Dimensional Relationship between Maxillary Anterior Teeth and Inter Hamular Distance - Shrestha, Ashwin; Mathema, S.R.B.; Maharjan, S.K.; Kam, S.L. (Journal of Nepalese Prosthodontic Society, 2018)
Introduction: Selection of anterior teeth for the fabrication of artificial denture during Prosthodontic rehabilitation is a complex process. Different authors have suggested various methods, however no single method can be used reliably to select artificial teeth. This study aims to assess dimensional relationship of maxillary anterior teeth with inter hamular distance which may assist in the artificial teeth selection. Materials and methods: This clinical study was carried out on 95dentate subjects meeting the inclusion criteria. Prior to impression making, hamular notch was located precisely with T-burnisher and was marked with indelible pencil. Impression of maxillary arch was made using irreversible hydrocolloid impression material and casts were poured using Type III dental stone. Measurements were made directly on the cast using digital vernier caliper. The contact point widths of maxillary right and left maxillary central incisors, lateral incisors and canines were measured. The distance between the right and left hamular notch was measured. The sum of contact point widths of all maxillary anterior teeth was calculated. All the data were recorded and statistically analyzed. Result: There is a positive correlation between combined width of maxillary anterior teeth and inter-hamular notch distance with Pearson’s correlation coefficient (r) 0.217 and p value 0.035 which is statistically significant. Conclusions: There is significant correlation between combined width of maxillary anterior teeth and distance between right and left hamular notch. This correlation is valuable and practicable in estimating the six maxillary anterior teeth width.